1993
DOI: 10.1093/oxfordjournals.bmb.a072625
|View full text |Cite
|
Sign up to set email alerts
|

An introduction to free radical biochemistry

Abstract: Free radicals are chemical species possessing an unpaired electron that can be considered as fragments of molecules and which are generally very reactive. They are produced continuously in cells either as accidental by-products of metabolism or deliberately during, for example, phagocytosis. The most important reactants in free radical biochemistry in aerobic cells are oxygen and its radical derivatives (superoxide and hydroxyl radical), hydrogen peroxide and transition metals. Cells have developed a comprehen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
524
0
53

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 913 publications
(584 citation statements)
references
References 0 publications
7
524
0
53
Order By: Relevance
“…The enzymes of endoplasmic reticulum such as cytochrome p-450 and b5 enzymes and diamine oxidase contribute to the formation of ROS [68]. Another important thiol oxidase enzyme, Erop1p catalyses the transfer of electrons from dithiols to molecular oxygen results in the formation of H 2 O 2 [69].…”
Section: Endoplasmic Reticulummentioning
confidence: 99%
See 1 more Smart Citation
“…The enzymes of endoplasmic reticulum such as cytochrome p-450 and b5 enzymes and diamine oxidase contribute to the formation of ROS [68]. Another important thiol oxidase enzyme, Erop1p catalyses the transfer of electrons from dithiols to molecular oxygen results in the formation of H 2 O 2 [69].…”
Section: Endoplasmic Reticulummentioning
confidence: 99%
“…The other endogenous sources of ROS include prostaglandin synthesis, auto-oxidation of adrenalin, phagocytic cells, reduced riboflavin, FMNH 2 , FADH 2 , cytochrome P 450, immune cell activation, inflammation, mental stress, excessive exercise, infection, cancer, aging, ischemia etc. [68].…”
Section: Endoplasmic Reticulummentioning
confidence: 99%
“…stabilization of membranes (Boldyrev et al, 1988), scavenging of free radical intermediates (Kohen et al, 1988;Salim-Hanna et al, 1991;Pavlov et al, 1993), chelation of divalent transition metals such as iron, copper and zinc (Brown, 1981;Kohen et al, 1988;Klebanov et al, 1998), elimination of lipid peroxidation products in a nonenzymatic way Dupin et al, 1987). These properties are strictly related to each other; for example, important compounds in free radical biochemistry, such as hydrogen peroxide, in the presence of transition metal ions produce the more reactive and damaging hydroxyl radical (Cheeseman and Slater, 1993). Recent studies, carried out on cultured fibroblasts, described an antisenescent effect of carnosine (McFarland and Holliday, 1994).…”
Section: Antioxidant Effectmentioning
confidence: 99%
“…8 It converts superoxide radicals (O 2 À ) in to hydrogen peroxide (H 2 O 2 ) and oxygen, and the hydrogen peroxide is metabolized by catalase and glutathione peroxidase. The human retina is rich in these proteins.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7] Developing tissue can be harmed as a result of the oxidative effect of oxygen radicals, which cause damage presumably by increasing the peroxidation of fatty acids or nucleic acids and eliminating protein cross-linking. 8 The multicentre trial of cryotherapy for ROP demonstrated that the risk of unfavourable outcome is 50% in 'threshold ROP' and that cryotherapy decreases this risk by nearly 35%. 9,10 Studies have shown that vitamin E might also mitigate the effect of antioxidants on ROP in humans.…”
Section: Introductionmentioning
confidence: 99%